Structural and semantically peculiarities of the mimical set expressions (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
Struktural and semantical peculiarities of one of the types of paralinguistic set expressions are examined in this article. Specifically the peculiarities of the mimical set expressions are examined; language experience of the nation, stereotype of its mentality were fixed in the mimical set expressions; emotional and power side of the life were reflected; ethnopsyhological character were coded in the mimical set expressions. The mimical set expressions are analysed according to the peculiarities of the look, the expression of eyes, mimical reactions, where separate parts of the face are taken part; the actions which demonstrate the physiological changes of face.
Keywords: paralinguistical set expression; mimical set expression; mimical reaction; physiological changes